Skillion Roof Design to Get Optimum Solar Radiation in Yogyakarta - Putra, Yudi Utomo; Asnawi, Rustam; Wardhany, Arum Kusuma (DPTE FT UNY, 2023)
Electrical energy is energy that cannot be released from daily activities at home, all elec-tronic equipment requires electrical energy, one source of electrical energy is the electrici-ty company PT. PLN (Persero) and as an alternative source of electrical energy, a home can use solar panels installed on the roof as a small scale power generator or can be called Solar Home System (SHS), but electrical energy obtained is very dependent on the radia-tion received by the solar panels, therefore, to obtain optimum solar radiation, it is neces-sary to calculate the azimuth angle and tilt angle which can be used as a reference for in-stalling solar panels. So mathematical calculations are needed to calculate the maximum azimuth angle and tilt angle. Mathematical modeling is used to calculate solar energy in-stalled at coordinates 7.7° south latitude, in that coordinate, average solar radiation can get from Meteorological, Climatological, and Geophysical Agency on horizontal surface, then calculation the declination angle, latitude angle, hour angle, azimuth angle and tilt angle to get value of incidence angle. Value of the declination angle, latitude angle, and hour angle are constant, while the azimuth angles divide into four directions, it's 0°, 90°, 180°, and 270° and the tilt angles are 20°, 25°, and 30° on skillion roof design. The results of the calculation and analysis of the movement of the sun for one year show that, by calculating the average solar radiation in a year, the roof of the house in the form of a skillion with an azimuth angle in the 0° gets the most optimal solar energy at an angle of 20° with an aver-age solar radiation of 442,96 W/m2 in one year.